Bundling Climate Smart Solutions with and for women smallholder farmers in Ghana - Obeng Adomaa, Faustina (2024)
Climate smart interventions need to address he peculiar needs of men, women and other vulnerable groups in order to build climate resilience of communities. Building of learnings from 2021-2023, this Info Note presents bundled climate solutions developed with and for women farmers to address the challenges of groudnut, cowpea and sweet potato production in Ghana. These bundled solutions brings together technical solutions and institutional arrangements to address the primary challenges that women groundnut, cowpea and sweet potato farmers face. The Info Note also presents pathway for scaling these bundled solutions